In situ detection of piRNA‐651 in exosomes and cells for cancer diagnosis by a new gold nanoparticle nucleic acid probe - Qin‐Xin Gao; Qian‐Qian Wu; Zhi‐Ying Dong; Xiao‐Yuan Qin; Lin‐Yan Zhai; Bao‐Ping Xie; Wen‐Jun Duan (Interdisciplinary Medicine)
Abstract Increasing studies have demonstrated that PIWI‐interacting RNAs (piRNAs) in circulating exosomes can serve as novel molecular biomarkers for tumor liquid biopsy. However, methods for in situ detection of piRNAs encased in exosomes are limited. In this study, we designed a spherical nucleic acid probe named piR‐651, which can enter exosomes simply by incubating with them for 2 h and in situ detect piR‐651 with a detection limit of 5 × 107 particles/μL. Based on this probe, we established a liquid biopsy method for the in situ detection of piR‐651 in plasma exosomes. The assay could distinguish the expression levels of piR‐651 between 21 breast cancer patients and 22 healthy individuals. The receiver operating characteristic curve shows an area under the curve as 0.9931 and the diagnostic sensitivity and specificity at the best cutoff are 85.7% and 100%, respectively. The probe can also easily perform in situ imaging of piR‐651 in living cells. To avoid low sensitivity and kinetics in detecting large‐sized PIWI‐interacting RNA complexes, we rationally designed the structure and detection scheme of piR‐651 probe, which was synthesized by modifying 13‐nm gold particles with high‐density Anchor‐Report DNA duplexes through the butanol dehydration method. The new design of the gold nanoparticle nucleic acid probe can be applied to the fabrication of nucleic acid probes targeting other large‐volume nucleic acids for developing more molecular biomarker‐based liquid biopsy for cancer diagnosis.